Water culture in Egypt - Gad A. (Water culture and water conflict in the Mediterranean area, 2008)
Egyptians, as religious people, drive lots of their culture features from their beliefs. The Bible referred that God instructed Profit Moses to strike a rock, and out of this flinty hardness flowed sufficient water to meet the needs of all people and their livestock, the Bible writers later saw this rock as a symbol of Christ. Quran has deepened the basic belief of water importance through the text, that all living organisms are originated from water. Throughout man's history, the basic requirement for water has led developing communities to be centralized along waterways due to the power and life sustaining qualities that water provides. Modern societies are often influenced by man's dependence on water for the sustenance of life. Runoff from hills, mountains, and plains, flowing across watersheds, and channeling water into nearby ponds, lakes, and rivers provides the moisture required to produce crops and support both animal and plant life on which man feeds. Rivers provide the means to transport grains, minerals, materials, products from one region to another. This article reviews the footprint of water importance in different phases of Egyptian culture though out the history.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)